2002
DOI: 10.1002/pd.415
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and postnatal characterization of Y chromosome structural anomalies by molecular cytogenetic analysis

Abstract: We describe three cases in which we used fluorescence in situ hybridization (FISH), polymerase chain reaction (PCR) and comparative genomic hybridization (CGH) to characterize Y chromosome structural anomalies, unidentifiable by conventional G-banding. Case 1 was a 46,X,+mar karyotype; FISH analysis revealed an entire marker chromosome highlighted after hybridization with the Y chromosome painting probe. The PCR study showed the presence of Y chromosome markers AMG and SY620 and the absence of SY143, SY254 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…There have been a number of previously reported cases of isodicentric Yp [Gaal et al, 1978; Hsu, 1994; Genuardi et al, 1995; Robinson et al, 1999; Hernardo et al, 2002; Yoshitsugu et al, 2003]. However, almost all cases to date have been mosaic cases, with the second cell line typically being 45,X.…”
Section: To the Editormentioning
confidence: 99%
“…There have been a number of previously reported cases of isodicentric Yp [Gaal et al, 1978; Hsu, 1994; Genuardi et al, 1995; Robinson et al, 1999; Hernardo et al, 2002; Yoshitsugu et al, 2003]. However, almost all cases to date have been mosaic cases, with the second cell line typically being 45,X.…”
Section: To the Editormentioning
confidence: 99%
“…In fact, most patients with idic(Y) are mosaic for an additional cell line, mostly 45,X [Robinson et al, 1999]. There is phenotypic variability among patients with 45,X/46,X, idic(Y) mosaicism [Hernando et al, 2002; DesGroseilliers et al, 2006] which was attributed to variable location of the breakpoints and to the proportion of 45,X cells distributed over the different tissues [Alvarez‐Nava et al, 2003; DesGroseilliers et al, 2006]. Idic(Y) causes a wide range of sex‐linked reproductive disorders, including spermatogenic failure, sex reversal, mixed gonadal dysgenesis, and Turner syndrome; accordingly the patients may have normal male external genitalia, ambiguous genitalia, or normal female genitalia [Hsu, 1994].…”
Section: Introductionmentioning
confidence: 99%
“…The routine G-band staining analysis indicated that the fetus had a mosaic karyotype with two marker chromosomes in three cell lines. The abnormal karyotype was 45,X [13]/46,X,+mar1 [6]/46,X,+mar2 [9], and the mosaic proportion was 46, 21 and 33% (13/28, 6/28 and 9/28 cells), respectively ( Fig. 1A-C).…”
Section: Resultsmentioning
confidence: 95%
“…A dicentric Y chromosome is a common abnormal structural rearrangement between sister chromatids and is unstable during cell division; therefore, it is highly likely to generate various cell lines, including 45,X and delY cell lines. Previous studies have mostly described individuals with ambiguous genitalia and mixed gonadal dysgenesis who were diagnosed with sex chromosome mosaicism postnatally (1,(8)(9)(10)(11)(12)(13)(14)(15)(16). However, there are few studies reporting prenatally diagnosed fetuses, particularly with three different cell lines.…”
Section: Introductionmentioning
confidence: 99%